Evaluation of Factors Influencing Choice of International Markets for Nigerian Export Firms - Iheanacho, Albert O.; Ifediora, Chuka; Okoh, Godwin L. (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2020)
This paper sets out to determine factors influencing choice of international markets for Nigerian Export firms. The paper objectives were to determine factors influencing Nigeria export firms’ choice for International markets engagement; to ascertain criteria for Nigerian export firms’ preference or selection of an international market and to examine the decision determinants of Nigeria export firms international marketing involvement. The population of the study is manufacturing companies in the NEPC membership list actively engaged in international marketing. Descriptive survey design was adopted in this study. A total of 90 manufacturing companies actively engaged in international marketing were randomly selected from the NEPC membership list. The research instrument was a structured questionnaire administered on the Marketing Executives of each of the ninety companies actively engaged in international marketing. Eighty two copies of the questionnaire (81%) were retrieved and used for the analysis. Both descriptive and inferential statistics were used in data processing. Simple percentage was used for descriptive analysis, while regression analysis was employed in testing the hypotheses with the aid of SPSS version 20 window. The study found that size and growth potential of the export market, economic factors and political factors are the most influential, and major determinants of the Nigerian  manufacturing firms’ that impact on the choice of their international export market and that there is positive relationship between ‘Nigerian export firms’ preference and selection of an international market. The study concludes that improving profit, gain business expansion and to increase sales in the international horizon are significant decision determinants of Nigeria Export firms’ choice for foreign markets to export their products.